Pakan Fermentasi Berbasis Bahan Lokal Berbentuk Pellet dan Tepung Terhadap Performa, Karkas dan Organ Intestinal Ayam Broiler - Manu, Kurnia Riwu; Mulyantini, N. G. A.; Kallau, Novalino H. G.; Telupere, Franky M. S.; Detha, Annytha I. R. (JURNAL KAJIAN VETERINER, 2023)
This study aims to examine the fermentation method on local feed in the form of mash and pellets on the performance, carcass and intestinal organs of broiler chickens. The livestock used were 144 CP 707 broiler chickens aged 21 days. The study used a completely randomized design with a 3x2 factorial pattern, namely 3 fermented feed treatments (F0 = non-fermented, F1 = fermented with Effective Microorganisms-4 (EM4), and F2 = Local Microorganism (MOL) fermented), and 2 forms of feed (B1 = mash, B2 = Pellet), so there were 6 treatment. Each treatment was repeated 6 times and each repetition consisted of 4 chickens. Parameters measured were the performance of broiler chickens, carcasses and intestinal organs. Data were analysed by ANOVA test and continued with Duncan's test. The results showed that feeding fermented Effective Microorganisms-4 (EM4) and Local Microorganism (MOL) had a significant effect on chicken performance and final weight (P<0.01), but no significant effect on carcass weight and percentage (P>0.05). As for the intestinal organs, feeding fermented Effective Microorganisms-4 (EM4) and Local Microorganism (MOL) had no significant effect on the percentage of liver, ventricle, proventriculus and small intestine (P>0.05) and had a significant effect on the length of the small intestine (P<0.01).